Post Traumatic Growth in Early Adults from Divorced Families - Ramadhan, Muhammad Rizky; Ginanjar, Adriana Soekandar; Djuwita, Efriyani (Universitas Medan Area, 2024)
Individuals with divorced parents are at high risk of developing post-traumatic stress disorder, but traumatic events can help individuals to learn things and develop competencies that they did not have before, which is called Post Traumatic Growth (PTG). The purpose of this study was to obtain a description of PTG from individuals who experienced parental divorce. The approach used in this study was phenomenological qualitative. The researcher conducted semi-structured interviews with six participants who experienced parental divorce as children or adolescents. Researchers used purposive sampling method in selecting participants. The results of the study concluded that all participants experienced changes in all dimensions of PTG after their parents divorced, namely changes in interpersonal relationships, changes in spiritual development, the emergence of appreciation for life, the emergence of new opportunities/priorities, and the emergence of self-strength after parental divorce